Theology without words : theology in the deaf community - Morris, Wayne, 1977- (Aldershot, England ; Burlington, VT : Ashgate Pub., 2008)
The author provides a discussion of the deaf community in Britain to reflect part of the international dimension of what it means to be a member of the community. She examines how the deaf approach their theology, how they have learned, understand and interpret images of God in the Bible, and what the content of their theology is.
The deaf community and their language -- A sense of deaf identity -- Talking with your hands : issues in British sign language -- In search of deaf theology -- Developing appropriate research methods -- Deafining and doing theology -- 'Anyone who has ears, let them hear'--but what about deaf people? -- Theology without words -- Theology without words : ecclesiology and liturgy -- Deaf in the image of the deaf God.
Includes bibliographical references (pages 161-175) and index.
Keywords: Church work with deaf people; Deaf people -- Religious life; Theology; Nonverbal communication